Implementation Of Innovation In The Perspective Of Educational Organizations In Pandemic Times - Ratna Wahyu Pusari; Suwito Eko Pramono; Fakhruddin Fakhruddin; Arief Yuliyanto (Universitas Negeri Semarang, 2023)
Innovation in education is an important thing to do by all stakeholders in education. Education dynamics are always changing rapidly, so a series of innovations are also carried out in human resources, infrastructure, financing, curriculum and others. The Covid-19 pandemic has left tasks that must be completed, but not all lines can accept the changes that have occurred. This article aims to see how innovation is implemented from the perspective of educational organizations after the Covid-19 pandemic.